A study of vitamin D status in children with tuberculosis in Peterborough, United Kingdom - Ahmed, Molla Imaduddin; Aslam, Mona (International Journal of Contemporary Pediatrics, 2017)
Background: We aimed to compare the prevalence of vitamin D deficiency and insufficiency in children with active or latent tuberculosis with the control population. Methods: This was a retrospective case control study and included 34 patients with evidence of exposure to tuberculosis and 34 controls reviewed at Peterborough city hospital from October 2011 to September 2013, who were matched with regards to age, gender and ethnicity. All patients had blood investigations, chest X-ray, Quantiferon Gold and Mantoux done at the time of review along with serum 25-hydroxyvitamin D concentrations in serum. Results: 73.6% of patients with Childhood Tuberculosis and 47.1 % of controls had low Vitamin D levels (deficiency and insufficiency). The median vitamin D level in children with tuberculosis was 34.75 nmol/l and in controls was 52.8 nmol/l. Patients older than 12 years of age had significantly lower serum 25-hydroxyvitamin D concentrations than those patients younger than 5 year of age. Gender, ethnicity, BMI, BCG status, serum calcium, serum phosphate and alkaline phosphatase had no significant correlation with vitamin D concentration in patients and controls. Conclusions: The present study demonstrated that children with evidence of exposure to Tuberculosis were more likely to be associated with lower levels of vitamin D than control population. Larger multi-centric randomized controlled trials are needed to prove the association between vitamin D and Tuberculosis. The association between low levels of vitamin D and tuberculosis suggests investigation for vitamin D deficiency in all children diagnosed with Tuberculosis and supplementation of these children with vitamin D.